DAYLIGHT PERFORMANCE IN SOUTH FACING ROOMS OF RESIDENTIAL APARTMENTS IN RESPECT OF CURRENT BUILDING CODE (2008): RELATION BETWEEN OBSTRUCTION DISTANCE AND OPENING SIZE - Afroz, Ruksana; Rahman, Md. Mostafizur; Tariqul Islam, Khandoker; Ahmed, Mushtaq (European Scientific Journal, ESJ, 2014)
Dhaka, the capital city of Bangladesh is one of the highly dense cities in the world. Demand of residence is increasing with the increasing number of population. Orientation of building and microclimate of surrounding varies a lot in this city. In tropical region where daylight is plenty in amount, south facing room gets blessing of sunlight almost fulltime in a day. What happen when surrounding situation changes because of following rules, building code (Floor Area Ratio, Set Back)? One size of land is selected to evaluate its daylight performance, where building volume and height is fixed. The experiment is done by computer simulation. The study was also based on the comparative analysis of the difference of opening size with the change of the building surroundings. The simulation was done by Eco-Tech software and no field survey was conducted. The research result concluded that the lighting condition of south facing room at different condition could control by changing the opening size. With the change of the percentage of opening can do better lighting environment at interior space.